Postresuscitative Morphofunctional Changes in the Brain and Retina (Experimental Study) - D. A. Yenikeyev; Ye. A. Nurgaleyeva; L. T. Idrisova; A. F. Samigullina; R. M. Gubaidullin; O. V. Laptev (Общая реаниматология, 2008)
Objective: to study changes in the microcirculatory bed and in the levels of nitric oxide in the rat brain and retina during a long (35-day) postresuscitative period. Materials and methods. A model of clinical death from acute circulatory arrest was used to evaluate the cerebral and retinal microvessels in the rat brain and retinal histological specimens (stained with hematoxylin-eosin and Indian ink) and to record the content of stable end metabolites of nitric oxide (nitric ions) in the study organs, by employing the Griss reaction. Results. The cerebral circulatory changes were characterized by significantly impaired vascular patency, decreased capillary network density, and a lower capillary diameter, which was most pronounced within the first 24 hours after resuscitation. The microcirculatory retinal circulatory disorders featured the staging of the course: vasodilatation and decreased capillary network density within the first 24 hours after resuscitation, followed by a progressive increase in the density of the capillary network from day 14, as compared with the control, and capillary diameter normalization. The study of nitric oxide metabolites in the cerebral cortex and retina of the experimental animals revealed their accumulation increase, that was statistically significantly 1.5 times greater or more than the control values, within 5 postresuscitative weeks. Conclusion. The long (35-day) postresuscitative period exhibited a heterodirectional change in the size and density of the cerebral and retinal microcirculatory network along with a parallel increase in the level of nitric oxide metabolites in the tissues of the rat cerebral cortex and retina. Key words: postresuscitation disease, cerebral microcirculation, ocular microcirculation, nitric ions.